Extraction of Keratin Protein from Chicken Feather - Gupta, Arun; Nuruldiyanah, Kamarudin; Chua, Gek Kee; R. M., Yunus (David Publishing, 2012)
The present research was conducted to extract keratin protein from chicken feathers. Protein is an important nutrient needed by our body to maintain body structures and is an important ingredient for cosmetic products. Chicken feathers have high level of keratin protein content and can become a suitable protein source. The main processes involved are first dissolving chicken feat hers using different reducing agents and later on separating the protein from chemicals. Reducing agents used are potassium cyanide, thioglycolic acid and sodium sulphide. Once the feathers are dissolved using reducing agents, ammonium sulfate solution is added to the solution for the precipitation of protein. The precipitated protein is washed with water several times and sodium hydroxide solution is used to obtain protein back in the solution form. Out of three different reducing agents used, sodium sulfide gives the highest efficiency in dissolving chicken feathers since the feathers are dissolved in a very short period of time. The percentage of keratin protein is evaluated by means of biuret test and FTIR analysis. The analysis by FTIR confirmed the presence of carboxyl acid and amino groups in the protein solution. The biuret test he lps in determining the concentration of protein obtained from different methods. Thus these two tests confirm the presence of protein in the solution. From this research, it can be concluded that protein can be extracted from chicken feathers. The keratin protein solution can be used for several purposes such as anti-aging cream, shampoo, and conditioner and for medical purposes such as bone replacement and bone graft.